A Stochastic Dynamic Model of Computer Viruses - Chunming Zhang; Yun Zhao; Yingjiang Wu; Shuwen Deng (Discrete Dynamics in Nature and Society)
A stochastic computer virus spread model is proposed and its dynamic behavior is fully investigated. Specifically, we prove the existence and uniqueness of positive solutions, and the stability of the virus-free equilibrium and viral equilibrium by constructing Lyapunov functions and applying Ito's formula. Some numerical simulations are finally given to illustrate our main results.